Levels Of Resistin And Visfatin In Patients With Metabolic Syndrome - Ginka Rayanova; Silvia Ganeva; Katya Todorova; Tsvetan Lukanov; Svetla Gecheva (Journal of Biomedical & Clinical Research)
The aim of the study is to investigate the serum levels of adipokines-resistin and visfatin in patients with metabolic syndrome. A prospective study was performed, including 153 (103 female, 50 male) subjects with metabolic syndrome. Carbohydrate metabolism was estimated by oral glucose tolerance test with 75g of glucose. Of the subjects investigated, 40 were with normal glycaemic tolerance, 40 - with impaired fasting glycaemia, 28 - with impaired glucose tolerance and 45 - with newly diagnosed diabetes mellitus type 2. The results were compared to those in a control group of 20 subjects without findings indicating metabolic syndrome. The serum levels of resistin and visfatin were measured with an enzyme immunoassay method (ELISA, BioVendor Laboratory Medicine, Inc., Czech Republic). There were significant differences in body mass index, waist circumference, systolic blood pressure, plasma level of blood glucose and serum level of triglycerides between the examined subjects with metabolic syndrome, as compared with the control group. The amount of serum resistin in subjects with metabolic syndrome and newly diagnosed diabetes mellitus type 2 was significantly higher, as compared to the controls. Subjects with metabolic syndrome and pathological glucose tolerance-impaired fasting glycaemia, impaired glucose tolerance and newly diagnosed diabetes mellitus type 2 were found with a significantly higher serum level of visfatin, as compared to normal glucose tolerance and to the controls. Subjects with metabolic syndrome and pathological glucose tolerance-impaired fasting glucose, impaired glucose tolerance and newly diagnosed diabetes mellitus type 2 exhibited significantly changes in serum levels of adipokines-resistin and visfatin.